LEGAL PROTECTION FOR HEIRS WHOSE INHERITANCE RIGHTS ARE IN THE POSSESSION OF ANOTHER HEIR BASED ON PRIVATE DEED OF GRANT - Diah Marla Pitaloka; Tjempaka Rusdam (Warmadewa Press, 2024)
This writing is motivated by inheritance problems in Court Decision Number 23/Pdt.G/2021/PN.Kkn with land as an inheritance which is currently the object of dispute, where for the legal heirs it would be unfair if his late father made a private deed of grant in which the contents donated all of his lands only to his heirs from the second wife. The lands that were supposed to become inherited assets were finally controlled by an heir only based on a private deed of grant. Of course, other heirs who feel that they have absolute rights (Legitieme Portie) do not accept that. This writing uses normative research methods, using library research on primary, secondary and tertiary legal materials. The conclusion from this writing is if a grant is made without the other heirs knowing or without approval of the other heirs and without considering the portion or reduction of the absolute part that should be owned by the other heirs, then when the other heirs do not agree to the grant and then file a lawsuit to cancel the grant, then the grant can be cancelled. Legal protection that can be given to other heirs whose inheritance is in the control of only one heir is the inherited lands that are the object of the dispute must be transferred to their legal heirs after being declared as the inheritance of the deceased which has not been divided as a form of wealth left behind.